Tathbiq Ta’lim Kitab "al-Arabiyyah Bayna Yadayk al-Juz’ al-Awwal" fi Ta’lim Maharat al-Kalam lada al-Tullab al-Marhala al-Thanawiyya fi Madrasah al-Hikmah al-Islami al-Alami Batu: تطبيق تعليم كتاب "العربية بين يديك الجزء الأول" في تعليم مهارة الكلام لدى الطلاب المرحلة الثانوية في مدرسة الحكمة الإسلامي العالمي باتو - Huda, Ahmad Nawirul Huda; Taufiq, R. Taufiqur Rochman; Ila, Nur Ila Ifawati (Tarling : Journal of Language Education, 2025)
Arabic language learning at Al-Hikmah International Islamic Boarding School Batu High School experiences obstacles in its efforts to improve students' speaking skills. This is due to the absence of textbooks that are in accordance with the Arabic language learning curriculum at the educational institution. With the above problems, researchers want to apply the Al-‘arabiyah Baina Yadaik Book which aims to improve students’ ability in speaking skills. The method used by researchers in this research is descriptive qualitative where data is collected through observation, interviews and documentation. This method was chosen so that researchers are able to describe, and describe real phenomena in accordance with the facts in the field, and without any engineering in it. The data sources in this study were all 12th grade students of Al-Hikmah IIBS Batu High School. The data analysis technique used consists of data collection as well as data reduction and conclusion drawing. The results of this study can be concluded that (1). the application of the Al-'arabiyah Baina Yadaik book at Al-Hikmah IIBS Batu High School includes three stages, namely a. Learning preparation stage (isti'dad) b. Learning implementation stage c. Learning closing stage. (2). To find out some of the supporting factors and inhibiting factors for learning Arabic using the Al-'arabiyah Baina Yadaik book at Al-Hikmah IIBS Batu High School